2011
DOI: 10.1007/s10549-011-1685-x
|View full text |Cite
|
Sign up to set email alerts
|

First-line bevacizumab in combination with weekly paclitaxel for metastatic breast cancer: efficacy and safety results from a large, open-label, single-arm Japanese study

Abstract: The high activity of first-line bevacizumab in combination with weekly paclitaxel observed in our study confirms the results of the E2100 trial. Our results suggest that the activity and tolerability of first-line bevacizumab-containing regimens demonstrated in E2100 can be reproduced in Japanese populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 39 publications
4
25
1
Order By: Relevance
“…In the present trial, the combination schedule of bevacizumab and paclitaxel as reported by Miller et al [1] resulted in a median PFS of 8.6 months, which was slightly shorter than the reported median PFS varying between 9.2 and 12.9 months obtained in the E2100 [1] and other phase II/III trials [21][22][23] of first-line paclitaxel plus bevacizumab (Appendix p. [15][16]. The precise reason for this discrepancy remains speculative.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…In the present trial, the combination schedule of bevacizumab and paclitaxel as reported by Miller et al [1] resulted in a median PFS of 8.6 months, which was slightly shorter than the reported median PFS varying between 9.2 and 12.9 months obtained in the E2100 [1] and other phase II/III trials [21][22][23] of first-line paclitaxel plus bevacizumab (Appendix p. [15][16]. The precise reason for this discrepancy remains speculative.…”
Section: Discussioncontrasting
confidence: 47%
“…The PFS rate at one year was 42% (95% CI 35-51) for ATX and 21% (95% CI [16][17][18][19][20][21][22][23][24][25][26][27][28][29] for AT.…”
Section: Efficacymentioning
confidence: 99%
“…However, unlike the results seen in the ovarian cancer setting, late-onset hypertension was remarkably infrequent in patients receiving bevacizumab for prolonged periods. In the single-arm JO19901 study, in which 120 Japanese patients received first-line bevacizumab in combination with paclitaxel for mBC, only a small number of patients developed proteinuria or hypertension in later cycles [13].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the BP regimen showed a shorter median OS of 15.4 months compared with 35.8 months in a study of first-line combined therapy with bevacizumab and paclitaxel in Japan 5 .…”
Section: Safetymentioning
confidence: 94%